2002
DOI: 10.1080/10715760290019354
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Pro-oxidant Effect of the Thiolic Compounds N -acetyl- l -cysteine and Glutathione against Free Radical-induced Lipid Peroxidation

Abstract: The antioxidant ability of thiol compounds has been the subject of much of the current research about oxidative stress. The direct scavenging of hydroxyl radicals by thiols has been suggested as their protection mechanisms. Nevertheless, the interaction of thiols with reactive radicals can generate thiyl radicals, which, in turn, may impart a pro-oxidant function. The purpose of this study has been to establish the effect of the thiol compounds N-acetyl-L-cysteine (NAC) and glutathione (GSH) against the peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
92
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(96 citation statements)
references
References 41 publications
2
92
1
1
Order By: Relevance
“…The essential intracellular reducing environment is maintained by the high ratio of reduced glutathione (GSH) to the oxidized disulfide (GSSG) form of glutathione (Schafer and Buettner 2001). The GSH/GSSG redox equilibrium regulates a pleiotropic range of functions that include nitrogen and oxygen free radical scavenger (Dickinson et al 2003), protein redox status and enzyme activity (Klatt and Lamas 2000), cell membrane integrity and signal transduction (Sagristá et al 2002;Dickinson and Forman 2002), transcription factor binding and gene expression (Deplancke and Gaskins 2002), phase II detoxification (Pastore et al 2003), and apoptosis (Hall 1999). Under normal physiologic conditions, glutathione reductase enzyme activity is sufficient to maintain the high GSH/GSSG redox ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The essential intracellular reducing environment is maintained by the high ratio of reduced glutathione (GSH) to the oxidized disulfide (GSSG) form of glutathione (Schafer and Buettner 2001). The GSH/GSSG redox equilibrium regulates a pleiotropic range of functions that include nitrogen and oxygen free radical scavenger (Dickinson et al 2003), protein redox status and enzyme activity (Klatt and Lamas 2000), cell membrane integrity and signal transduction (Sagristá et al 2002;Dickinson and Forman 2002), transcription factor binding and gene expression (Deplancke and Gaskins 2002), phase II detoxification (Pastore et al 2003), and apoptosis (Hall 1999). Under normal physiologic conditions, glutathione reductase enzyme activity is sufficient to maintain the high GSH/GSSG redox ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In basketball players, TBARS level directly correlated with PC in both training periods, indicating an integration of the peroxidation with the carbonylation process. It has been known that lipid radicals induce protein damage, and oppositely, thiyl radicals can cause the peroxidation of lipids, such as arachidonic acid (Sagrista et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There is need for non-toxic and inexpensive drugs for clinical radiation protection. Antioxidant agents may help protect against chemically induced or radiation induced toxicity in rats (5). Previous studies have indicated that some commonly used antioxidants of plant origin include vitamin E, vitamin C, selenium, phenolic compounds, carotenoids and flavonoids (6).…”
mentioning
confidence: 99%